Web 2.0/social media: 'the times they are a changing' - Hamill, Jim (Henry Stewart Talks, 2010)
What is Web 2.0?, Performance measures, The customer experience of the brand, Applications of Web 2.0, Internal and external use, Business impact, Web 2.0 in action, Review and recommendation sites, Building contacts and finding customers and partners, Social network sites, Sports marketing 2.0, Business opportunities and benefits, Strategy development, Balanced scorecard 2.0 strategy map, Obstacles and barriers
Archived at 2022/04/12